Buffalo in Borneo, Sarawak: A review of the current status of the indigenous buffalo industry - Abang Abdul Khalex, Abang Mohd. Harizt; Syed Hussain, Sharifah Salmah; Ramanoon, Siti Zubaidah; Sarbini, Shahrul Razid; Hassan, Mohammad Nasir; Nating, William Rovina; Asut, Robine; Abit, Lirong Yu; Kamaludeen, Juriah (Lifescience Global, 2021)
The Malaysian water buffalo, Bubalus bubalis, has traditionally been important livestock for the local people of Sarawak. Buffalo, other ruminants, and non-ruminants are essential for the livestock industry as they supply the largest source of protein for the entire nation. Cattle provide the largest production in the livestock industry at 0.2%, followed by other ruminants, including goats (0.1%), sheep (0.04%) and buffalo (0.03%). Water buffalo, or 'kerbau sawah' as it is locally known, is an overlooked animal compared to other livestock. Amidst the growing demand for beef within the domestic consumer market, the buffalo population in Sarawak has risen over the past 5 years from 5,396 to 6,205 heads in 2019. However, the self-sufficiency level (SSL) of cattle and buffalo beef has dropped from 26% in 2013 to 21.6% in 2019 despite the rising demand for local produce. Malaysia continues to import frozen buffalo beef from India and live bovine from other countries in order to meet domestic demands and support the growth of the local buffalo industry. Due to this, the Department of Veterinary Services (DVS) Sarawak introduced a buffalo yard program ('Natad Kerbau') to assist the state smallholder farmers in managing their buffaloes better. This paper focuses on describing the current status of buffalo production in Sarawak, its important functions (including provision for food security) and future prospects of B. bubalis in the livestock industry of Malaysia and Sarawak in particular.